Central pontine myelinolysis in a chronic alcoholic: A clinical and brain magnetic resonance imaging follow-up - Dujmović Irena; Vitas Jelena; Zlatarić Nataša; Drulović Jelena (Vojnosanitetski Pregled)
Introduction. Central pontine myelinolysis (CPM) is a noninflammatory, demyelinating lesion usually localised in the basis pontis. Chronic alcoholism is frequently associated with this condition which may have a variable clinical outcome. Until now, brain magnetic resonance imaging (MRI) follow-up in alcoholic CPM cases after alcohol withdrawal has been rarely described. Case report. We reported a 30- year-old male with a 12-year history of alcohol abuse, who presented with inability to stand and walk, nausea, vomiting and somnolence. Neurological examination revealed: impared fixation on lateral gaze, dysarthria, mild spastic quadriparesis, truncal and extremity ataxia, sock-like hypesthesia and moderate decrease in vibration sense in legs. Brain MRI showed a trident-shaped non-enhancing pontine lesion highly suggestive of CPM. After an eight-month alcoholfree follow-up period, the patient’s clinical status significantly improved, while the extent of MRI pontine lesion was merely slightly reduced. Conclusion. The presented case demonstrates that CPM in chronic alcoholics may have a benign clinical course after alcohol withdrawal, which is not necessarily associated with the reduction of lesions on brain MRI. [Projekat Ministarstva nauke Republike Srbije, br. 175031]